2018
DOI: 10.1136/jclinpath-2018-205293
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for the diagnosis of venous thromboembolism: D-dimer, thrombin generation, procoagulant phospholipid and soluble P-selectin

Abstract: Our results confirmed D-dimer as the main biomarker of VTE and speculated a role for sP-selectin. The impact of thrombin generation was limited and no role emerged for the PPL clotting time. These observations need to be confirmed in large management studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
31
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 24 publications
6
31
1
2
Order By: Relevance
“…TGA have showed prolonged time to peak (T max ) and time to initiation of coagulation (T lag ) in acute VTE, possibly related to consumption of coagulation factors in the formation of the thrombus. [8][9][10][11][12] In contrast, other studies have found an increased total thrombin generating capacity measured as the area under the curve (AUC), 8,9 which would not be the case after consumption of coagulation factors. Similarly, an increased thrombin generating capacity has been demonstrated in intermediate and serious thrombophilic phenotypes 13 and has been associated with an increased risk of first VTE and unprovoked recurrent VTE, 14,15 although there are conflicting results.…”
Section: Introductionmentioning
confidence: 90%
“…TGA have showed prolonged time to peak (T max ) and time to initiation of coagulation (T lag ) in acute VTE, possibly related to consumption of coagulation factors in the formation of the thrombus. [8][9][10][11][12] In contrast, other studies have found an increased total thrombin generating capacity measured as the area under the curve (AUC), 8,9 which would not be the case after consumption of coagulation factors. Similarly, an increased thrombin generating capacity has been demonstrated in intermediate and serious thrombophilic phenotypes 13 and has been associated with an increased risk of first VTE and unprovoked recurrent VTE, 14,15 although there are conflicting results.…”
Section: Introductionmentioning
confidence: 90%
“…When platelet activation occurs, a greater amount of thrombin is generated during the amplification and propagation of the coagulation cascade, resulting in an exponential increase of thrombin . Thrombin is considered the key enzyme of the coagulation system.…”
Section: Introductionmentioning
confidence: 99%
“…When platelet activation occurs, a greater amount of thrombin is generated during the amplification and propagation of the coagulation cascade, resulting in an exponential increase of thrombin. [13][14][15][16][17] Thrombin is considered the key enzyme of the coagulation system. The thrombin generation test (TGT) has emerged as a tool capable of assessing global hemostasis in a more physiological manner than conventional tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Також не впливала на рівні РФД-15 та Галектину-3 наявність у хворих супутньої фібриляції передсердь. Значне та достовірне зниження рівня Р-селектину у хворих з фібриляцією передсердь повязане з прийомом пероральних антикоагулянтів, які блокують продукцію тромбоцитами Рселектину цими хворими [17]. Резюме.…”
unclassified